A Review on Voice Control Home Environment to Ease of Use for Disabled Persons - Malakar, Anjali; Prajapati, Anubha (International Journal of Computer Sciences and Engineering, 2025)
This era is famous for digital automations which turned our lives more comfortable and effective. Almost every home appliances control through remote device or automatic accordingly. It’s very easy to put remote aside and use when required but for disabled person whose life is not easy as we have. They survives in their daily lives which indeed harder than normal people. So, we require more intelligent systems which may control through voice command with high level of accuracy which turn their life easier. We have so many home appliances which require turning off or on timely to aware from any casualty. This paper proposed an intelligent system which is able to turn home appliances control through voice commands. This paper also reviewed the existing systems which are based on voice control feature.